Antwerpen : de haven - Van Cauwenbergh, George; Van Cauwenbergh, Dis; Craeybeckx, Lode (Antwerpen : Ontwikkeling, 1961)
Bibliotheek Camille Huysmans
Nederlands
Monografie
Keywords: haven van Antwerpen